Interaction of the Left–Right Somatosensory Pathways in Patients With Thalamic Hemorrhage: A Case Report - Ishii, Daisuke; Ishibashi, Kiyoshige; Takeda, Kotaro; Yuine, Hiroshi; Yamamoto, Satoshi; Kaku, Yuki; Yozu, Arito; Kohno, Yutaka (Frontiers in Human Neuroscience, 2021)
Neural plasticity compensates for the loss of motor function after stroke. However, whether neural plasticity occurs in the somatosensory pathways after stroke is unknown. We investigated the left–right somatosensory interaction in two hemorrhagic patients using a paired somatosensory evoked potentials (p-SEPs) recorded at CP3 and CP4, which was defined as an amplitude difference between the SEPs of paired median nerve stimulations to both sides and that of single stimulation to the affected side. Patient 1 (61-year-old, left thalamic hemorrhage) has a moderate motor impairment, severe sensory deficit, and complained of pain in the affected right upper limb. Patient 2 (72-year-old, right thalamic hemorrhage) had slight motor and sensory impairments with no complaints of pain. Single SEPs were obtained by stimulation of the right and left median nerves, respectively. For paired stimulations, 1 ms after the first stimulation to the non-affected side, followed by a second stimulation to the affected side. In patient 1, a single SEP with stimulation to the non-affected side and a p-SEP were observed in CP4. However, a single SEP was not observed in either hemisphere with stimulation to the affected side. On the other hand, in patient 2, a single SEP in CP3 with stimulation to the non-affected side and in CP4 with stimulation to the affected side were observed; however, a p-SEP was not observed. In addition, to investigate the mechanism by which ipsilateral median nerve stimulation enhances contralateral p-SEP in patient 1, we compared the SEP averaged over the first 250 epochs with the SEP averaged over the second 250 epochs (total number of epochs recorded: 500). The results showed that in the patient 1, when the bilateral median nerve was stimulated continuously, the habituation did not occur and the response was larger than that of the single SEP with unilateral median nerve stimulation. In the current case report, the damage to the thalamus may cause neuroplasticity in terms of the left–right interaction (e.g., left and right S1). The somatosensory input from the affected side may interfere with the habituation of the contralateral somatosensory system and conversely increase the response.